Photoswitchable CAR-T Cell Function In Vitro and In Vivo via a Cleavable Mediator. Issue 1 (21st January 2021) - Zhang, Bo; Wang, Yan; Huang, Shenlong; Sun, Jiaqi; Wang, Min; Ma, Wenxiao; You, Yanbo; Wu, Ling; Hu, Jin; Song, Wei; Liu, Xudong; Li, Shengjie; et al.
Summary: Chimeric antigen receptor (CAR)-T-based therapeutics are a breakthrough in cancer treatment; however, they are hampered by constitutive activation, which leads to worrisome side effects. Engineering CAR-T cells to be as tightly controllable as possible remains a topic of ongoing investigation. Here, we report a photoswitchable approach that uses a mediator for the at-will regulation of CAR-T cells. This mediator carries dual folate and fluorescein isothiocyanate moieties tethered by an ortho-nitrobenzyl ester photocleavable linker. CAR-T cells were shown to be highly cytotoxic to targeted cells only in the presence of the mediator and acted in a dose-dependent manner. The toxicity of CAR-T cells can be rapidly terminated by cleavage of the mediator, and the effects of CAR-T cells can be activated again by resupplementation with the mediator without compromising tumor therapy. The approach described here provides a direction for enhancing the controllability of CAR-T cells and can likely be applied in other immunotherapies. Graphical Abstract: Highlights: Folate-O-FITC switch CAR-T cells to an activated state in a dose-dependent manner CAR-T-induced cytotoxicity can be rapidly terminated by the cleavage of folate-O-FITC CAR-T can be turned on/off on demand by supplementation/cleavage of folate-O-FITC Such switchable regulated manner would not compromise antitumor effects of CAR-T cells Abstract : CAR-T is a powerful technology for cancer therapy, but is largely limited by inherent controllability issues. Zhang et al. developed an accurate controllable approach based on the bond-cleavage chemistry combined with universal anti-FITC CAR-T cells, allowing the regulation of CAR-T cells in a switchable manner.